Integrated Assessment of Shoreline Change along the Calypsostranda (Svalbard) from Remote Sensing, Field Survey and GIS. Issue 5 (2nd September 2020) - Zagórski, Piotr; Jarosz, Kamila; Superson, Józef
Abstract: Arctic coasts are sensitive indicators of polar environment change. Here we present the results of a study that examines the coastal morphodynamics of the Calypsostranda coastline in Svalbard (High Arctic) between 2007 to 2017 and compare these short-term changes to previous studies for the period 1936–2007. During the 2007–2017 study period, the study area lost ca. 10, 710 m 2, at a mean Net Shoreline Movement (NSM) of −1.86 m and End Point Rate (EPR) −0.19 m/yr. Erosion also dominated between 1936–2007, −28, 800 m 2, at a mean NSM of −4.99 m and EPR −0.07 m/yr. Using EPR and Linear Regression Rate (LRR) parameters, we divide the Calypsostranda coastline into eroding and aggrading zones. The overall pattern of coastline change during the two study periods is similar, but the rate of erosion is higher in the recent interval, reflecting stronger climate-driven processes. Recent climate warming in the study area has been accompanied by an intensification of extreme events such as storms (e.g. ocean swell). The situation is becoming more pronounced due to the progressively reduced period of winter shore ice. Depending on the anemometric conditions, the Calypsostranda coast is modified by wind waves, and consequently longshore currents and associated sediment movement.